Knowing and Unknowing Purchases of Undeclared Healthcare Goods and Services: The Role of Vertical and Horizontal Trust - Ioana Alexandra Horodnic (MDPI AG, 2021)
Although major advances have been made in relation to explaining the supply side of the informal economy, this is not the case for the demand-side of the informal economy. This study analyses for the first time the purchasers of undeclared goods and services in the healthcare sector. To evaluate the purchase of undeclared healthcare goods and services, logistic regression analysis and robustness tests are used on 3048 interviews in Cyprus, Greece, Italy and Malta. The finding is that an important share of the purchasers make this type of purchase unknowingly. However, no difference in terms of socio-economics characteristics of those who knowingly and those who unknowingly made purchases of undeclared healthcare goods and services was identified. Meanwhile a significant influence of trust (in government and in other citizens) has been identified in relation to those who made these purchases knowingly. As such, policy measures aimed at decreasing unknowing purchases and at nurturing trust are discussed in the concluding section.